Промисел тюленя в життєзабезпеченні алгонкінів Лабрадору: приморський компонент тайгової культури - Воробйов, Д. (Народна творчість та етнографія, 2010)
Охарактеризована система природопользования северных алгонкинов. Обстоятельно проанализирована роль охоты на тюленя в системе их жизнедеятельности. На основании археологических и письменных источников доказано, что, невзирая на акультурацию, связанную с европейской колонизацией, индейцы Лабрадора остались носителями таёжной адаптации со свойственным ей типом культуры. The System of the nature’s usage of the Northern Algonquins is characterized and the role of seal-hunting in their system of vital functions is analyzed. Founded on the archeological and writing sources it is argued that without regard to acculturation connected with the European colonization the Labrador Indians (aboriginals) remained the carriers of taiga adaptation with its own cultural type.